UNICEF’s role in promoting the social responsibility of entrepreneurs for the benefit of children’s education and social protection in developing countries - MolkAra, Melika; Mahmoodi Fard, Alireza; Khorsand, Elham; Salehi, Kimia (International Journal of Business Management and Entrepreneurship, 2025)
Extreme weather events, rising temperatures, and shifting rainfall patterns pose significant threats to developing countries with fragile social, economic, and political structures. Social protection is particularly important for children, in view of their higher levels of vulnerability compared to adults, and the role that social protection can play in ensuring adequate nutrition, access to and utilization of social services. While existing evidence shows that social protection programmes successfully address several dimensions of child well-being often in an indirect way - a move towards a more "child sensitive" approach to social protection has recently been advocated at the highest level in the international development community. While research has intensified on socioeconomic impacts of climate change, existing survey studies exhibit substantial scope variations and seldom concurrently analyze these impacts, hindering policy coordination. This study reviews literature on the broad spectrum of socioeconomic impacts of climate change to discern trends and underscore areas requiring additional attention. The survey unveils that, across various socioeconomic indicators, the most vulnerable groups bear a disproportionate burden of climate change, with long-term impacts forecasted to surpass medium-term effects. Adaptation and mitigation options are feasible but must be tailored to local contexts. Financial matters, corporate social responsibility (CSR), climate change, and other sustainable solutions all work in tandem. In order to provide a thorough understanding of the integration between various components during crises, it is necessary to provide knowledge of the interaction between financial, societal, and environmental aspects. In order to accomplish this, hundreds of papers were examined and presented using bibliometric analysis. The study demonstrated that, when examining financial crises in relation to CSR and climate change, sustainability issues were clearly examined. Sustainability, environmental economics, governance approaches, and sustainable development are some of the main issues in this comprehensive subject. Besides, the emerging topics that need more research include organizational resilience, global financial crises, and sustainable performance, while there are no specific themes developed in the subject matter that integrate financial crises, CSR, and climate change.